Electrophoretic Deposition of Chitosan Films Doped with Nd2Ti2O7 Nanoparticles as Protective Coatings against Corrosion in Saline Solutions - M. Martinez-Gomez; A. Quinto-Hernandez; N. S. Flores-Garcia; Jan Mayén; M. Dominguez-Diaz; H. Martinez; J. Porcayo-Calderon; J. G. Gonzalez-Rodriguez; L. Martinez-Gomez (International Journal of Polymer Science)
In this study, the electrophoretic deposition of chitosan films doped with Nd2Ti2O7 nanoparticles was carried out as corrosion protection systems for exposed materials in aqueous environments rich in chlorides. Completely crystalline Nd2Ti2O7 nanoparticles with an average size of 100-200 nm were obtained. Electrophoretic deposition of chitosan films with Nd2Ti2O7 nanoparticles was possible. With a working voltage of 5 V and 20 minutes of deposition, homogenous chitosan films with a thickness of 4 microns were obtained. According to the FT-IR (Fourier transform infrared spectroscopy), Raman, and XRD (X-ray diffraction) analyses, it was observed that the presence of the nanoparticles modified the properties of the chitosan films, that is, their crystallinity was increased and their moisture absorption capacity was reduced. These modifications caused a better performance against the corrosion of chitosan films deposited on 1018 carbon steel. Its electrochemical evaluation showed that the chitosan films perform as cathodic coatings by affecting the oxygen reduction reaction. This was possible due to the barrier effect of the Nd2Ti2O7 nanoparticles, by blocking the effective area for the diffusion of the aggressive electrolyte species.